Task Revision: A Neglected Form of Work Performance - Staw, Barry M.; Boettger, Richard (Academy of Management Journal, 1990)
This study addressed the problem of task revision, a virtually unresearched issue in the work performance literature. We defined task revision as action taken to correct a faulty procedure, an inaccurate job description, or a role expectation that is dysfunctional for an organization. Two experiments were constructed to measure task revision and test for its determinants. Results showed that goal setting inhibited task revision: instructions to ?do your best? were superior to a specific goal. Facilitators of task revision were the salience of alternatives and being in a supervisory position with accountability pressures. We discuss the implications of these results in terms of the functions of counter-role behavior for organizations and the need to broaden the construct of work performance.